Review of the book by A. Kh. Abashidze, M. V. Fedorov, I. A. Chistokhodova “The Law of Foreign Relations”, Moscow, RUDN University, 2007. - A. A. Kovalev (Московский журнал международного права, 2007)
The book under review is the first one in Russian legal literature, which gives the comprehensive analysis of four major types of foreign representation: diplomatic representatives, consular offices, special missions, and permanent representatives of states at the international organizations.The authors of the book rightly use the term the law of foreign relations instead of diplomatic or consular relations, as the latter does not include the whole scope of the issue. In the book the history of formation of this sphere of law is given. It is necessary to remark that authors pay attention to a very important issue – the one of international legal personality as a condition for settling up foreign representations. Another crucial aspect considered by the authors is the question of special and particularized foreign representations and their functions. Authors also provide a classification of special missions and use for this purpose different criteria. It should be noted that authors manage to find new approaches to topics which were already meticulously researched. One of the major advantages of the book is that theoretical and practical questions are analyzed simultaneously. Authors also touch upon the issue of formation of the institute of diplomatic asylum, the notion of which is still very vague.Evaluating the results of the research on the law of foreign relations presented in this book it is necessary to underline the fact that the book is a major scientific analysis of the problems of the law of foreign relations and has a very important both theoretical and practical meaning.